2011
DOI: 10.1002/jemt.21042
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolyticaelectrondense granules secretion in vitro and in vivo: Ultrastructural study

Abstract: Electron dense granules (EDGs) were identified by transmission electron microscopy in Entamoeba histolytica trophozoites recovered from hamster liver lesions. Abundant granules were present in trophozoites recovered after 15 min of liver inoculation. Variation in the size and morphology of these EDGs was also observed. Numerous granules were present in the plasma membrane when these parasites were incubated for 5 min with MDCK monolayers. Release of these EDGs was suggested by the presence of granules in conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In a recent study, Chávez Munguia et al [35] demonstrated that electron-dense granules contain multiple cysteine protease activities.…”
Section: Extracellular Protozoamentioning
confidence: 99%
“…In a recent study, Chávez Munguia et al [35] demonstrated that electron-dense granules contain multiple cysteine protease activities.…”
Section: Extracellular Protozoamentioning
confidence: 99%
“…Contact‐dependent release of EDGs has been reported in E. histolytica and N. fowleri following incubation with cultured epithelial cells or collagen substrates (Chávez‐Munguía et al. , ). Release of these granules has also been observed during excystation in A. castellanii, N. fowleri, and E. invadens (Chávez‐Munguía et al.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have reported that release of EDGs may be induced through contact with collagen or epithelial cells (Chávez‐Munguía et al. ; Martínez‐Palomo et al. ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a correlation between collagenolytic activity and virulence was observed when the levels of activity of different strains (virulent HM-1:IMSS and the less virulent 200-NIH and HK-9) [139–141] or of other virulence factors [142] were compared, suggesting that collagenase may play a role in the pathogenesis of amoebiasis. In a recent study, Chavez-Munguia et al [143] demonstrated that electron-dense granules contain multiple CP activities. …”
Section: Entamoeba Histolyticamentioning
confidence: 99%